The behavior of Coastal Families Related to the Household Waste Management for the Sustainability of Marine Resources using gender Approach in Kapoposang Islands, South Sulawesi - Etnayanti, Etnayanti; E.Fachry, Mardiana; Zubair, Hazairin (International Journal of Environment, Agriculture and Biotechnology, 2021)
Kapoposang Islands is one of the many islands in South Sulawesi which has small island development characteristics and a marine tourism park that serves as a marine conservation area and marine tourism site. These main features lead to the many activities performed by the community that may potentially damage the marine ecosystem. This study aims to understand the behavior of coastal families, both men and women through their roles and activities in household waste management that may support the sustainability of marine resources. Samples were determined through random sampling and a total of 18 families from 4 villages was selected. This study used a qualitative approach and descriptive correlational analysis. The results showed that there were two family activities that may potentially produce household waste: (1) domestic activity and (2) economic activity such as fishing and home industry such as fish processing and coconut oil production. The family’s knowledge about household waste (38.8%) and plastic that does not decompose (11.1%) was low. This affected family behavior where 72.2% of women disposed their household waste into the sea compared to 30% of men disposing their fishing waste into the sea. Little support from the village government in household waste management contributed to these behaviors, with only 27.8% samples ever attended recycling training and there was no final waste disposal available on the islands. The conclusion is that the predominant behavior of coastal families in household waste management remains harmful to the environment because of the low support from the village government in providing training activities and facilitation.